STRATEGIES FOR OPTIMIZING EFFICIENCY AND PRODUCTIVITY IN SCHEDULING COMPANY ACTIVITIES - Suryani, Lilis (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This research aims to investigate the scheduling of company activities in the Banten area with a focus on optimizing efficiency and productivity. Through a descriptive-qualitative approach, local environmental factors, the role of technology, as well as interdepartmental collaboration and data analysis are explored to understand the challenges and opportunities in activity scheduling. Data was collected through interviews and observations of companies in Banten. Findings from the research indicate that local environmental factors, such as markets, infrastructure, and regulations, have a significant impact on the scheduling of company activities. Information technology and collaboration between departments have the potential to improve operational efficiency. Meanwhile, data analysis provides valuable information to improve the quality of decision making. These findings indicate the importance of an integrated approach in improving company activity scheduling in Banten